Eye dominance and minor physical anomalies in schizophrenia: relations between two biological markers of abnormal neurodevelopment - Akabalieva, Katerina (Frontiers in Psychiatry, 2023)
Background: To investigate the frequency of left eye dominance and minor physical anomalies (MPAs) in schizophrenic and control subjects and determine the interrelations of these two biological markers of neuronal dysontogenesis in schizophrenia. Subjects and methods: Three tests for eye dominance were administered as performance tasks, not preference questionnaires. Seven MPAs were examined. The sample consisted of 180 (98 schizophrenic and 82 control) subjects. Several statistical methods for examining the eye tests separately and together were used to assess the difference in left-eyedness between schizophrenic and control subjects. Results: Left eye dominance is significantly higher in schizophrenic subjects. Left-eyed subjects are more stigmatized with MPAs. There is a strong positive correlation between left-eyedness and stigmatization with MPAs in schizophrenic patients. Conclusions: As hand dominance is under cultural pressure, eye dominance is a useful, reliable and culturally independent indicator of altered hemispheric lateralization. The significant positive correlations between left-eyedness and MPAs and the high concurrence of these biological markers in schizophrenic patients are a potent indicator of underlying aberrant neurodevelopment.